2014
DOI: 10.1037/a0036945
|View full text |Cite
|
Sign up to set email alerts
|

Giving back or giving up: Native American student experiences in science and engineering.

Abstract: Native Americans are underrepresented in science, technology, engineering, and math (STEM) careers. We examine communal goal incongruence-the mismatch between students' emphasis on communal work goals and the noncommunal culture of STEM-as a possible factor in this underrepresentation. First, we surveyed 80 Native American STEM freshmen and found they more highly endorsed communal goals than individualistic work goals. Next, we surveyed 96 Native American and White American students in STEM and non-STEM majors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(221 citation statements)
references
References 82 publications
(149 reference statements)
9
165
1
Order By: Relevance
“…In line with recent work showing that helping parents see the personal utility of math and science improves their high-school sons and daughters' motivation for the fields (Harackiewicz et al 2012), our findings go one step further and suggest that not all ''utility'' values are equal when considering improving women's science identity. Instead, communal utility in particular (compared to agentic utility for example) may be important for educators and scholars to consider when designing and delivering classroom interventions aimed at broadening the participation of women in science (and other underrepresented minority groups, see Smith et al 2014a). Our results imply that women's identification with science may be enhanced when the communal utility value of physics is made salient, which remains to be tested in future research.…”
Section: Discussionmentioning
confidence: 61%
“…In line with recent work showing that helping parents see the personal utility of math and science improves their high-school sons and daughters' motivation for the fields (Harackiewicz et al 2012), our findings go one step further and suggest that not all ''utility'' values are equal when considering improving women's science identity. Instead, communal utility in particular (compared to agentic utility for example) may be important for educators and scholars to consider when designing and delivering classroom interventions aimed at broadening the participation of women in science (and other underrepresented minority groups, see Smith et al 2014a). Our results imply that women's identification with science may be enhanced when the communal utility value of physics is made salient, which remains to be tested in future research.…”
Section: Discussionmentioning
confidence: 61%
“…Johnson (2012) found that women of color in STEM had lower sense of belonging compared to their counterparts from other groups. Additionally, women and URM students may perceive a lack of fit between their identities or values and a major or career in STEM (Diekman et al 2010;Smith et al 2014); this mismatch may further augment a false sense that they do not belong. In turn, as is suggested by the work of Thoman and colleagues (2014), sense of belonging (or a lack thereof) can work as a force to push women out of STEM fields, where they may feel low levels of belonging, and toward non-STEM fields where they are more likely to feel a sense of fit.…”
Section: Sense Of Belongingmentioning
confidence: 99%
“…Such a posture goes against the very nature of the human species and the reality of scientific knowledge production as a "community effort comprising innumerable interdependent contributions" (Casadevall & Fang, 2012, p. 893). Furthermore, for students of color and women, individualistic approaches are largely contrary to more prevalent community-focused or collectivist approaches that may be active in their communities of origin and/or socialization (Coon & Kemmelmeier, 2001;Gaines et al, 1997;J. L. Smith, Cech, Metz, Huntoon, & Moyer, 2014;Su, Rounds, & Armstrong, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such arrangements promote beneficial peer interactions, and address the need for an environment wherein the cultural foundations of students and junior faculty are integrated in the mentoring process. All of these are identifiable as factors contributing to or detracting from the success of the aforementioned populations (Ackelsberg et al, 2009;Davidson & Foster-Johnson, 2001;Dodson et al, 2009;Ellis, 2001;Gasman et al, 2008;Johnson-Bailey, 2004;Johnson-Bailey et al, 2009;King & Chepyator-Thomson, 1996;Patterson-Stewart et al, 1997;J. L. Smith et al, 2014;Thomas et al, 2007).…”
Section: Perspectives On the Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation